On five-level tone contrasts: the case of Dan-Gblewo - Akinlabi, Akinbiyi; Ahoua, Firmin; Gondo, Bleu Gildas (Stellenbosch Papers in Linguistics Plus, 2022)
The central goal of this research is to propose that no language utilizes more than four level pitches contrastively (from low to high). The central question is whether a five- or six-way contrast represents five or six level tones, or a combination of level tones, contour tones, voice quality, and syllable type. We argue that Dan-Gblewo operates a four-level-plus-creaky-voice system rather than a five-level tone system. We show that Dan must be analysed as such from the empirical, experimental, and theoretical perspectives.